2017
DOI: 10.1002/2016wr020252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Tracer Choice and End‐Member Definitions on Hydrograph Separation Results Across Nested, Seasonally Cold Watersheds

Abstract: Isotope‐based hydrograph separation (IHS) is a widely used method in studies of runoff generation and streamflow partitioning. Challenges in choosing and characterizing appropriate tracers and end‐members have, however led to presumably highly uncertain IHS results. Here we tested the effects of end‐member definitions and tracer choices on IHS results in nested Prairie watersheds of varying size and landscape characteristics. Specifically, the consideration of eight potential “new” water end‐members, eight pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Bedrock fractures also maintain a permanent hydraulic link between the incised stream channel and the groundwater table, thus making HWY240 the only outlet where perennial, albeit at times stagnant or slow‐moving, water is observed. A recent study using isotope‐based hydrograph separation (Bansah & Ali, ) also confirmed the predominance of “old” streamwater at this site, as long as the “old water” end‐member was portrayed by water collected from an 8 m‐deep well (and not from piezometer with intake depths of 1.5 m or less). As for streamflow at the Miami site, it is mainly fed by Hortonian overland flow and deep groundwater flow from the Miami aquifer (Betcher et al, ).…”
Section: Methodssupporting
confidence: 64%
See 3 more Smart Citations
“…Bedrock fractures also maintain a permanent hydraulic link between the incised stream channel and the groundwater table, thus making HWY240 the only outlet where perennial, albeit at times stagnant or slow‐moving, water is observed. A recent study using isotope‐based hydrograph separation (Bansah & Ali, ) also confirmed the predominance of “old” streamwater at this site, as long as the “old water” end‐member was portrayed by water collected from an 8 m‐deep well (and not from piezometer with intake depths of 1.5 m or less). As for streamflow at the Miami site, it is mainly fed by Hortonian overland flow and deep groundwater flow from the Miami aquifer (Betcher et al, ).…”
Section: Methodssupporting
confidence: 64%
“…In general, the δ 18 O streamwater timeseries were slightly damped compared with δ 18 O precipitation timeseries in both sampling years. Early spring δ 18 O data showed the strongest evidence of depletion in heavy isotopes (Figure ), as do snow and snowmelt samples in that region (Bansah & Ali, ), whereas summer and fall samples were the most enriched. Open‐water evaporation effects were visible through d‐excess data: Streamflow d‐excess values were slightly higher during periods of very low to no flow—albeit with quasistagnant water—in the channels, especially at the headwater “MS” sites (Figure ).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, (i) event waters and pre‐event waters sometimes have similar isotope compositions (e.g., two occasions in data set published by Berman et al, ); (ii) event water (e.g., rain and snowmelt) isotope compositions often vary substantially through time (e.g., Liu et al, ; Munksgaard et al, ; Xu et al, ; Zuecco et al, ); (iii) pre‐event water (e.g., groundwater) isotope compositions can vary through time (Haiyan et al, ); (iv) soil water discharges can generate substantial streamflow (e.g., Iwagami et al, ); and (v) surface water stores can contribute to runoff (e.g., Gibson, Birks, & Yi, ; Jefferson et al, ). Even where all five assumptions appear valid, end‐member δ 18 O values often vary, yielding large uncertainties in pre‐event water fractions (Bansah & Ali, ; Joerin et al, ).…”
Section: Groundwater Discharges To Riversmentioning
confidence: 99%